Scientific activity of Leonid Ivanovich Rubtsov in the Soviet Subtropics - O.L. Rubtsova; N.V. Chuvikina (Інтродукція Рослин, 2018)
Objective – to study the first years of scientific work of the wellknown dendrologist, landscape architect L.I. Rubtsov.